2020
DOI: 10.7202/1068866ar
|View full text |Cite
|
Sign up to set email alerts
|

Jumping through hoops: An overview of the experiences and perspectives of Aboriginal mothers involved with child welfare in Manitoba

Abstract: This article provides an overview of the experiences of Aboriginal mothers involved with child welfare in Manitoba. Jumping through hoops was a prominent perspective evident in stories and reflections that Aboriginal mothers shared about their experiences with child welfare and legal systems. The research drew upon interviews and talking circles conducted with Aboriginal women, and included interviews conducted with community advocates and lawyers in the spring and summer of 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Indigenous women encounter additional barriers directly related to colonization such as intergenerational trauma, residential schools, the Sixties Scoop phenomenon, and socioeconomic struggles (Aguiar & Halseth, 2015;Bennett, 2008Bennett, , 2009Carriere & Richardson, 2009;Chen et al, 2015;Cull, 2006;Evans-Campbell, 2008;Ing, 2006;Johnston, 1983;McKenzie, Varcoe, Brown, & Day, 2016;Niccols, Dell, & Clarke, 2009;Rousseau, 2015;Shahram et al, 2017), that are presented in the literature review. Research also revealed that between 70% and 80% of children in care of the British Columbia government are of Indigenous descent (Ministry of Children and Family Development, 2010;McKenzie et al, 2016;O'Donnell et al, 2010;Rousseau, 2015Rousseau, , 2018Trocme, Knoke, & Blackstock, 2004).…”
Section: Research Significancementioning
confidence: 99%
See 4 more Smart Citations
“…Indigenous women encounter additional barriers directly related to colonization such as intergenerational trauma, residential schools, the Sixties Scoop phenomenon, and socioeconomic struggles (Aguiar & Halseth, 2015;Bennett, 2008Bennett, , 2009Carriere & Richardson, 2009;Chen et al, 2015;Cull, 2006;Evans-Campbell, 2008;Ing, 2006;Johnston, 1983;McKenzie, Varcoe, Brown, & Day, 2016;Niccols, Dell, & Clarke, 2009;Rousseau, 2015;Shahram et al, 2017), that are presented in the literature review. Research also revealed that between 70% and 80% of children in care of the British Columbia government are of Indigenous descent (Ministry of Children and Family Development, 2010;McKenzie et al, 2016;O'Donnell et al, 2010;Rousseau, 2015Rousseau, , 2018Trocme, Knoke, & Blackstock, 2004).…”
Section: Research Significancementioning
confidence: 99%
“…Indigenous women often turn to alcohol and drugs to numb their pain because of the aforementioned barriers (Bennett 2008(Bennett , 2009Evans-Campbell, 2008;Taplin & Mattick, 2015). Substance abuse interventions consequently often play a large part in the child welfare system in order to mitigate the risk to the child (Bennett, 2008;Crowe-Salazar, 2012;Perry, Newman, Hunter, & Dunlop, 2015;Reid, Greaves, & Poole, 2008;Taplin & Mattick, 2015).…”
Section: Research Significancementioning
confidence: 99%
See 3 more Smart Citations